ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN PERMASALAHAN TRIGONOMETRI DITINJAU DARI GENDER BERDASARKAN NEWMAN - Savitri, Dhea Ayunda; Yuliani, Anik (IKIP Siliwangi, 2020)
This research was held to find the factors behind Students'error, which later will be classified into high, average, and low capability, and the influence of gender onÂ finishing trigonometry problem-based test. The writer used qualitative descriptive research design. The subject of this research consisted of 36 Students', which later will be sorted into a group of 6 containing 3 male and 3 female Students'. The writer used interview as the data collection technique for this research. And the data analysis technique was divided into three steps: data reduction, data presentation, and data verification-conclusion. Analysis framework was developed using the Newman Theory. The results of t his research shows that there are different kind of errors conducted by male and female students. Female students made less errors in comprehension and process skill steps than the male students. Meanwhile on transformation and encoding steps, male students Made less errors than the female students.